Tumular mounds (Confluenţe Bibliologice, 2021)
This article inserts the history of treasures or the multitude of tumul, mounds of antiquity and prehistory, legacies of the Scythians, Geth, Greeks, mounds scattered everywhere: tumul from Constanța, around Mangalia. In Bessarabia there are tumul in the Balti area; Saharna Nuoa, Tiglau; on a high plateau on the right bank of the Dniester River; near Iezarenii Vechi, Sangerei district. The author highlights their presence and location, the forms, the territorial arrangement that is still preserved, the opinions of the specialists.
Keywords: burial habits; tumulus